Mengungkap Peran Penting Bakteri Asam Laktat dalam Fermentasi Mandai (Artocarpus integer) : Studi Isolasi dan Karakterisasi - Nailla Indayani Sumardi; Ardi Mustakim (International Forum of Researchers and Lecturers, 2025)
Mandai is a traditional fermented food made from the inner skin of the cempedak fruit (Artocarpus champeden) and is widely known in South Kalimantan. Its distinctive sour taste is a result of microbial activity during the natural fermentation process. This study highlights the important role of lactic acid bacteria (LAB) as the dominant agents in Mandai fermentation. The main objective of this research is to isolate and characterize LAB from fermented Mandai samples. The methods used in this study include serial dilution, inoculation on Nutrient Agar (NA) media, incubation at room temperature, colony morphology observation, and Gram staining using crystal violet. The results showed the presence of round colonies with a creamy white color and smooth surfaces, which indicate the characteristics of lactic acid bacteria. Most of the isolates showed Gram-positive properties, supporting their identification as lactic acid bacteria. This research not only enriches our understanding of the microbial ecology in Mandai fermentation but also opens up opportunities for utilizing LAB as a natural preservative or functional probiotic in both traditional and modern food products. The presence of LAB in Mandai fermentation suggests the potential to enhance the quality and health benefits of this traditional food, making it a viable source of probiotics beneficial for digestive health. Additionally, the use of LAB in Mandai processing could increase the appeal of this product in broader markets, both locally and internationally. Overall, this study provides a solid foundation for further development in utilizing microbes in traditional food fermentations. Moreover, it opens opportunities to improve the quality and sustainability of Mandai products while raising awareness about the importance of fermentation in enhancing the nutritional value and health benefits of traditional food products.